Synthesis and characterizations of mof-5 materials by nonsurfactant templating method for ammonia storage - Othman S.Z.; Misran H.; Aminuddin A.M.; Salim M.A.; Shah N.N.H.; Razak N.A.A. (Microscopy Society of Malaysia, 2023)
Metal-organic frameworks (MOF-5) with non-surfactant templating method were successfully synthesized with cubic and tetragonal structure at ca. 0.26-0.63 m. The syntheses were conducted at ambient condition, i.e. room temperature and pressure. Three types of fatty alcohols with different chain length were used namely octyl alcohol, decyl alcohol and dodecyl alcohol. The results suggested that fatty alcohol chain length affected the relative crystallinity, morphology and competitive ammonia adsorption properties of MOF-5. MOF-5 synthesized with longer carbon chain fatty alcohol i.e. dodecyl alcohol resulted in higher relative crystallinity and higher ammonia uptake up to c.a. 4.6%. However, exposure to ammonia partially destroyed the crystal structure. 2019, Microscopy Society of Malaysia. All rights reserved.